Recent advances on graphyne and its family members as membrane materials for water purification and desalination - Lasisi, Kayode Hassan; Abass, Olusegun K.; Zhang, Kaisong; Ajibade, Temitope Fausat; Ajibade, Fidelis Odedishemi; Ojediran, John O.; Okonofua, Ehizonomhen Solomon; Adewumi, James Rotimi; Ibikunle, Peter D. (Frontiers in Chemistry, 2023)
Graphyne and its family members (GFMs) are allotropes of carbon (a class of 2D materials) having unique properties in form of structures, pores and atom hybridizations. Owing to their unique properties, GFMs have been widely utilized in various practical and theoretical applications. In the past decade, GFMs have received considerable attention in the area of water purification and desalination, especially in theoretical and computational aspects. More recently, GFMs have shown greater prospects in achieving optimal separation performance than the experimentally derived commercial polyamide membranes. In this review, recent theoretical and computational advances made in the GFMs research as it relates to water purification and desalination are summarized. Brief details on the properties of GFMs and the commonly used computational methods were described. More specifically, we systematically reviewed the various computational approaches employed with emphasis on the predicted permeability and selectivity of the GFM membranes. Finally, the current challenges limiting their large-scale practical applications coupled with the possible research directions for overcoming the challenges are proposed.